Effectiveness of Different Pedagogy in Management Studies - Sunuwar, Seema (The International Research Journal of Management Science, 2016)
The main purpose of this study is to determine perception of the different pedagogy methods among undergraduate students and faculties in a management college. The study is a primary research conducted using questionnaire and interview method at Nepal College of Management, Nepal. The result of the study shows that the students found lecture using power point presentations as the most effective one followed by case studies methods and audio video teaching, whereas lecture using power point presentations followed by audio video based teaching as the most easy to understand as well as recall. The faculties’ opined case based study and brainstorming methods as the most effective method of teaching. The study also indicates that there is significant relationship between ease of understanding the pedagogy and its effectiveness as well as between ease to recall the lessons learnt using the pedagogy and its effectiveness.